Combined thermomechanical and optical simulations of planar-optical polymer waveguides. (29th October 2020) - Suar, Monali; Baran, Murat; Günther, Axel; Roth, Bernhard
Abstract: In this work, we describe a theoretical approach for combined thermal, mechanical and optical simulation and analysis of planar polymer waveguides. We consider a finite element approach for thermal and stress/deformation simulation. Also, a Crank-Nicholson finite difference beam propagation method (CN-BPM) is implemented to perform the optical simulation. The results of the finite element (thermo-mechanical) analysis are coupled with the CN-BPM results to carry out the optical simulation of poly(methyl methacrylate) (PMMA) waveguides as function of temperature. For thermal simulation, a model was designed where a polysilicon microheater was added to the upper cladding of the PMMA waveguides to vary the temperature between 20 °C and 200 °C. Thus, the impact of the induced temperature gradients on the refractive index modulation of the PMMA waveguides and the corresponding change in numerical aperture are obtained. In addition, the temperature gradients influence the beam intensity profiles and the movement of the primary eyes within the optical waveguides, thus, impacting the optical properties. Furthermore, the thermally induced mechanical stress and deformation were calculated for transverse and axial directions. In the next step, validation of the model by systematic experimental studies will be performed. In general, our approach provides a toolbox for more comprehensive multi-physics theoretical analysis of polymer-optical waveguides which, in future, can be extended to more complex and functional structures as required for flexible sensor networks, as example.